Studi Karakteristik Fisikokimia dan Organoleptik Bubuk Kopi dari Biji Cacat Hitam Kopi Robusta dengan Perbedaan Suhu Penyangraian - Anggraini, Arisca Putri; Damat, Damat; Manshur, Hanif Alamudin (Universitas Muhammadiyah Malang, 2023)
This research studied the effect of the level of black coffee bean defects and roasting temperature on the physicochemical content of coffee powder and the organoleptic content of robusta coffee brewing. This research used a factorial Randomized Complete Block Design (RCBD) with two replications. Parameters in this study, namely moisture content, ash content, pH, caffeine content, color intensity, and sensory. Data analysis in this research used ANOVA at the 5% level and a DMRT follow-up test. The research result show that there is an interaction between the treatment of the type of defective beans and roasting temperature on moisture content, ash, pH, color intensity of robusta coffee powder, and organoleptic brewing of robusta coffee. Different types of defective beans significantly affected the moisture content, ash, pH, caffeine, and color intensity of robusta coffee powder, while differences in roasting temperature significantly affected the water content, ash, pH, caffeine, and color intensity of robusta coffee powder. The best treatment for all physicochemical and organoleptic parameters is partially black beans with a roasting temperature of 180 °C.